“Kambakutaisoto” and Emotional Instability Associated With Premenstrual Syndrome - Shiota, Atsuko; Shime, Chika; Nakai, Kyoko; Kageyama, Mitsuru (Frontiers in Nutrition, 2021)
Many women suffer from premenstrual syndrome (PMS), which can be said to be a modern illness in this busy society, and mental symptoms such as irritability often affect the surroundings and cause loss of self-confidence. The symptoms of PMS are diverse, and it is often difficult to treat with psychiatric and social symptoms with low-dose estrogen progestin combination drug (LEP) alone. Selective serotonin reuptake inhibitors (SSRIs) are also effective, but many cannot take them because of their side effects. “Kambakutaisoto” is a Kampo medicine consisting of "jujube,” "licorice" and "wheat,” which is often described as "food,” but it is highly effective in treating emotional instability caused by PMS in sensitive young women. There are many reports on the effects of Kampo medicine. The molecular nutritional findings of Kampo medicine, which has dramatic effects despite its mild herbal composition, have also been reported, suggesting an association with premenstrual exacerbation of functional hypoglycemia. A narrative review of its clinical effects on PMS and the results of molecular nutrition studies was performed.